(3GdLGeY aj GdTQMs - (3CHh GdMSjf RjO Hf eMeO GdcdGQis; (3CHh WGdH jMji Hf GdMSjf Hf GdbGSe Hf gGQhf Hf CHj YjSi Hf Ydj GdgGQhfj,J (B424 (3g` s
(3ChdgG (B:s
(3cJGH GdfcGM (B: (3GdCUd ai GdfcGM GdcJGH hGdSfI hGdELeGY s
(3BNQgG (B:s
(3eSGdI (B: (3aEf de jcf dg CH , aGdCe Chdi Hg eGde JJRhL , aEf JRhLJ NjQ GdUHi Hjf Ceg hHjf YUHg hGdYGOI LGQjI HCf GdYUHI dGjHdZhf ai GdMfh Ydi GdhdO eHdZ GdCe hjHdZ SHY Sfjf Ch KeGfi Sfjf s
(3fSNI eUMMIs
(3YfGhjf GdaUhd hGdeSGFd HGdSejcs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B141s
Keywords: (3Gdabg GdESdGejs